2015
DOI: 10.1371/journal.pone.0142871
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Proteomics-Based Approach to Identification of Immunodominant Antigens from a Complex Pathogen: Application to the CD4 T Cell Response against Human Herpesvirus 6B

Abstract: Most of humanity is chronically infected with human herpesvirus 6 (HHV-6), with viral replication controlled at least in part by a poorly characterized CD4 T cell response. Identification of viral epitopes recognized by CD4 T cells is complicated by the large size of the herpesvirus genome and a low frequency of circulating T cells responding to the virus. Here, we present an alternative to classical epitope mapping approaches used to identify major targets of the T cell response to a complex pathogen like HHV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 72 publications
(87 reference statements)
2
20
0
Order By: Relevance
“…Six different HHV‐6B proteins, including structural and nonstructural viral proteins, were found to be sources for the eluted peptides. Three of the source proteins, the tegument protein U11 and the viral glycoproteins U39 and U48 (gB and gH, respectively), previously have been shown to be targeted by CD4 Tcell responses , but the epitopes are newly identified here. Three HHV‐6B proteins were newly identified as targets for the CD4 T‐cell response: the capsid protein U56, the hypothetical protein U63, and the glycoprotein U85.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Six different HHV‐6B proteins, including structural and nonstructural viral proteins, were found to be sources for the eluted peptides. Three of the source proteins, the tegument protein U11 and the viral glycoproteins U39 and U48 (gB and gH, respectively), previously have been shown to be targeted by CD4 Tcell responses , but the epitopes are newly identified here. Three HHV‐6B proteins were newly identified as targets for the CD4 T‐cell response: the capsid protein U56, the hypothetical protein U63, and the glycoprotein U85.…”
Section: Discussionmentioning
confidence: 85%
“…To increase understanding of how HHV‐6B is recognized and controlled by the cellular immune system, we used an approach not previously applied to this virus, in which naturally processed and presented peptides bound to cellular MHC proteins are identified by immunoaffinity purification, acid elution, and characterization by mass spectrometry. The 25 peptides identified here, corresponding to six distinct immunodominant epitopes, can be added to the set of MHC‐I and MHC‐II epitopes derived from HHV‐6A/B that have already been published . The source of MHC‐II complexes in our studies was the T‐lymphoblastoid cell line SupT1, which is highly susceptible to infection with HHV‐6B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 5 are annotated as having immediate early, 14 are annotated as having early, and 18 are annotated as having late expression kinetics. Eleven of these HHV-6B ORFs have not, to our knowledge, previously been described as HHV-6B CD4 T-cell antigens (30,31,35). Unlike the originally annotated U83 (NCBI accession number NC_000898.1), the reannotated ORF "U83A" was transcribed in the reverse direction and contained one intron, resulting in an entirely new amino acid sequence; interestingly, the full-length U83A protein elicited responses from three donors, supporting its status as a novel HHV-6B ORF.…”
mentioning
confidence: 85%
“…These studies have identified HHV-6 U11, U14, U54, and U90, the homologs of CMV UL32, UL25, UL82/83, and IE1, respectively, as targets for CD4 or CD8 T cells (31)(32)(33)(34). Other studies have taken a cross-sectional approach by testing libraries of peptides that were predicted to bind to a particular HLA allele: DRB1*0101 for CD4 T cells (30,35) or HLA-B*0801 for CD8 T cells (36). These studies expanded the number of known T-cell antigens considerably but were limited to single HLA allelic variants.…”
mentioning
confidence: 99%